Hypomagnesaemia causing myopathy and hypocalcaemia in an alcoholic. Issue 742 (August 1987) - Pall, H. S.; Williams, A. C.; Heath, D. A.; Sheppard, M.; Wilson, R.
Abstract : A well-nourished alcoholic patient developed a subacute myopathy which responded rapidly to correction of severe hypomagnesaemia. The finding of profound hypocalcaemia prompted the measurement of serum magnesium. Magnesium deficiency should be looked for in any alcoholic patient with a myopathy as the prognosis seems better than in many other forms of alcoholic myopathy. Correction of the magnesium deficiency corrects the hypocalcaemia without the need for calcium supplementation.